(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To find out the difference between tubotympanic and atticoantral type of chronic suppurative otitis media in their presentation, complications and hearing impairment they produce. Methods: This cross sectional study done in the department of Otolaryngology of Mymensingh Medical College Hospital and Bangabandhu Sheikh Mujib Medical University, during the period of January 2005 to February 2006. For this study 100 Patients who were diagnosed as a case of chronic suppurative otitis media by detailed history, clinical examination and related investigations were collected. Results: In this study majority of the patients were within 10-20 years of age & male female ratio 2.1:1. This condition was common in rural population with low socio economic status having poor nutrition and those who take bath in river or pond water in rural area. Common presentation of tubotympanic type of CSOM was aural discharge and deafness but presentation of atticdntral type of CSOM was aural discharge and deafness with other symptoms like earache, fever, headache tinnitus and vertigo, etc. Hearing loss was found more in atticoantral type of disease. Complication of CSOM was found only in atticoantral type of disease. Conclusion: Complications are more frequent and hearing impairment is morein severity in case of atticoantral type of chronic suppurative otitis media Key word: CSOM; Tubotympanic; Atticoantral. DOI: 10.3329/bjo.v16i2.6846 Bangladesh J Otorhinolaryngol 2010; 16(2): 113-119